Studies on the Specific Fibrinolytic Effect of Human Extrinsic (Tissue-Type) Plasminogen Activator in Human Blood and in Various Animal Species in Vitro - Korninger, C; Collen, D (Thrombosis and Haemostasis, 1981)
Human extrinsic (tissue-type) plasminogen activator (EPA) was highly purified from the culture fluid of a human melanoma cell line, both as a one-chain or as a two-chain molecule. Its specific fibrinolytic effect on human whole blood clots or plasma clots with different degrees of fibrin crosslinking was evaluated in an in vitro system, composed of a 125I-fibrin labeled clot, hanging in circulating human plasma. After infusion of EPA (30 IU per ml over 3 hrs), non-crosslinked clots lysed more extensively (75-100 percent in 5 hrs) than totally-crosslinked clots (50-65 percent), and no difference was found between one-chain or two-chain EPA. The extent of lysis of totally-crosslinked human or animal plasma clots hanging in autologous plasma induced by EPA varied markedly from one species to the other. When 90 IU of EPA were infused over 3 hrs, crosslinked human plasma clots dissolved for over 95 percent within 5 hrs. Under comparable conditions, the degree of lysis was 80 percent in primate plasma (cynomolgus fascicularis), 60 percent in cat and rabbit plasma, 30 percent in dog plasma and only 10 percent in rat plasma. Systemic activation of the fibrinolytic system in the circulating plasmas was minor and dose-dependent in all species, but complete fibrinogen breakdown was not observed in any species following infusion of up to 90 IU EPA per ml plasma.It is concluded that the human system is more susceptible to EPA induced fibrinolysis than the other animal systems which were investigated, and that even totally-crosslinked clots can be lysed after infusion of EPA.
Keywords: Extrinsic (tissue-type) plasminogen activator; Thrombolysis of crosslinked clots; Thrombolytic/fibrinogenolytic ratio; Species variability